Introduction and mechanical evaluation of a novel 3rd-generation medium manganese AHSS with 86 GPa% of PSE - Sedaghat-Nejad, Ramtin; Shahverdi, Hmid Reza; Askari-Paykani, Mohsen (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2022)
Reduction in weight and energy consumption is among the most concerning subjects in the automotive industry. To date, advanced high-strength steel (AHSS) has been one of the best solutions to reach this objective. However, this material involves high chemical composition and production processing costs. This paper introduces a new grade of third-generation medium Mn AHSS with extraordinary mechanical properties. Regarding its product of strength and elongation (PSE), i.e., 86 GPa%, this is the highest value of PSE of an AHSS reported until now to the best of the author's knowledge. Also, because of using 13 wt% of Mn, lower Mn has been used than conventional twinning-induced plasticity (TWIP) steels, and mechanical properties have been improved. The samples were fabricated using a vacuum induction furnace (VIM) and heat-treated at four different temperatures to perform austenite reversion transformation (ART). The best sample (i.e., the one with the highest PSE) was microstructurally evaluated and compared to the as-rolled one. In addition, the effect of different heat treatment temperatures on mechanical properties was observed. The difference in mechanical properties is mainly related to different austenite stabilities and fractions. Intercritical annealing formed lamellar austenite layers with varying levels of stability. These layers caused the TRIP to stay active during the whole deformation process. Since this structure can also delay necking, high elongation was achieved along with high strength.